2015
DOI: 10.1016/j.ijsu.2015.04.093
|View full text |Cite
|
Sign up to set email alerts
|

Metastases of pancreatic adenocarcinoma: A systematic review of literature and a new functional concept

Abstract: An updated insight into the world of Pancreatic Tumors might help physicians in better evaluating mechanisms of metastases, patients selection and survival and in programming appropriate interventions to modify the worst outcomes of advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 125 publications
0
28
0
Order By: Relevance
“…Most pancreatic tumors are located in the head of pancreas (47-65%), followed by the body and tail (15-18%) 4 . Tobacco smoking, diabetes mellitus, obesity, heavy alcohol drinking, family history, certain genetic polymorphisms, and chronic pancreatitis have been considered as risk factors for pancreatic adenocarcinoma 5 . Surgical resection remains the only potentially curative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Most pancreatic tumors are located in the head of pancreas (47-65%), followed by the body and tail (15-18%) 4 . Tobacco smoking, diabetes mellitus, obesity, heavy alcohol drinking, family history, certain genetic polymorphisms, and chronic pancreatitis have been considered as risk factors for pancreatic adenocarcinoma 5 . Surgical resection remains the only potentially curative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, histological examination of tissues taken from animals sacrificed at the same early time-point from both cohorts of mice revealed that mice injected with AsPC-1 WT cells had pronounced adenocarcinoma tumor cell presence in both the lung and the peritoneum (red arrow, representative images, Figure 6B and Supplementary Figure 13), organ commonly associated with PDAC metastasis [39], while mice injected with AsPC-1 MOE cells had normal lung and peritoneal tissue upon harvest (green arrow, representative images, Figure 6B and Supplementary Figure 13). Taken together, these data show that expression of MTSS1 plays a critical role in the suppression of cell invasion and migration in vitro ; moreover, increasing MTSS1 expression in metastatic cells increases survival in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…An extensive systematic literature review was performed by Cannistra and colleagues to determine the impact and outcomes of metastasis in pancreatic cancer [10]. Most studies…”
Section: Plos Onementioning
confidence: 99%
“…Randomized trials have addressed resection combined with perioperative chemotherapy in colorectal cancer and have reported better outcomes using these strategies. Several case series have pointed out benefit of locoregional treatments in liver metastasis in MPC, but randomized data on the subject are scarce [10,27]. Our results show that liver metastasis confer a HR for death of 1.53 with 95% CI of 1.15 to 2.02 (p-value 0.003), without significant heterogeneity (I2 = 5.03%) and a HR for risk of relapse of 1.96 with 95% CI of 1.28 to 2.99 (p-value 0.002).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation